Education, Dominance and Identity
X, 243 p.
Keywords: This volume is a collection of research cases illustrating the interrelationships among education, dominance and identity in historical- and contemporary contexts. The cases reflect particular ways in which local-, group, and indigenous identities have been affected by a dominant discourse, how education can support or undermine identity, and how languages (including dominant and sub-dominant languages) and the language of instruction in schools are at the centre of challenges to hegemony and domination in many situations. Examining the issues in their research, the contributors reveal how members of minority-, disadvantaged-, or dominated groups (and the teachers and parents of children in their schools) struggle for recognition, for education in their own language, for acceptance within larger society, or for recognition of the validity of their responses to reform initiatives and policies that address a wider agenda but that fail to take into account key factors such as perceptions and subaltern status. Collectively, the chapters document research employing a variety of methodological approaches and theoretical perspectives, illustrating an array of universal and global issues in the field of comparative and international education. However, each of the cases its own unique character, as research findings and as personal reflections based on the authors’ experiential knowledge in particular social, cultural and political contexts. The contexts and regional settings include Chile, Canada, the United States, Hungary and elsewhere in East-Central Europe, France, Germany, Spain, Malaysia, Tanzania, South Africa, Cyprus, Tunisia, Egypt, Iran and elsewhere in the Middle East.